The Fookien Times Philippines Yearbook. (Manila, Philippines : The Fookien Times Yearbook Publishing Co., Inc., 1977)
The 60th anniversary edition of the Philippines Yearbook of the Fookien times presents outstanding articles and reviews of the country's condition on the previous year. It includes special anniversary section, The Philippine yearbook destination and centennial section. It drives historians and researchers to a true picture of the previous years' events in the country.
Chapter 1. -- Population and Housing -- Chapter 2. Income and Prices -- Chapter 3. Economic accounts -- Chapter 4. Environment and natural resources -- Chapter 5. Agriculture -- Chapter 6. Industry Sector -- Chapter 7. Foreign trade -- Chapter 8. Tourism -- Chapter 9. Vital, Health and Nutrition Statistics -- Chapter 10. Education -- Chapter 11. Labor and Employment -- Chapter 12. Social services -- Chapter 13. Transportation and Communication -- Chapter 14. Energy and water resources -- Chapter 15. Public administration -- Chapter 16. Banking and Finance -- Chapter 17. Public order, safety, and justice -- Chapter 18. Science and Technology -- Chapter 19. International statistics.
Includes bibliographical references and index.
Keywords: STATISTICAL YEAR BOOK